(untitled) (Philology, 2020)
The subject-matter of the analysis in this article is the moral and aesthetic philosophy of the great Bulgarian humanist Yordan Yovkov. The objective is to find out how the author, through the literary characters in his short stories “Song of the Wheels”, “On the Wire” and “Last Joy”, finds a brilliant and masterly way towards the universal spiritual values by means of the national mindset. In the spirit of Yovkov’s aesthetics and his most cherished dream for a harmonious human community based on the principles of the good, beauty and love, the author makes an effort to scrutinize the psychology and the spiritual makeup of his literary characters Mokanina, Drugoseleca, Sali Yashar and the eccentric Lyuckan. Based on this one can easily come to the artistic generalizations of the moral and aesthetic messages of the author who strongly believes that the world could become better and more equitable when every single individual strives to become a better and more equitable person. Even today Yovkov’s wise rendition of the question “How should one live?” sounds contemporary and is absolutely necessary for us: in his views, the meaning of life is to do good, to create beauty in all its forms, to strive for harmony deep within our own self and with the people around us as well as with Nature. The study purposefully leads to the conclusion that Yovkov’s characters are eternal with their ability for empathy and the way in which they understand the meaning of their existence as well as their creative attitude towards labour and the ability to love dedicatedly, until death, with their explicit renunciation of war “being the greatest disaster on Earth” and with their capability for moral rebirth.